PENGARUH PENDIDIKAN PELATIHAN, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR - Rispantyo, Sri Indarti & (Universitas Slamet Riyadi, 2009)
ABSTRACT The purpose of the research are followed to know the significant influence of variable: (1) In service training to the performance of teacher.(2) Motivation to the performance of Teacher. (3) Work Environment to the performance of Teacher. (4) In service training, motivation, and work environment to gether to the performance of teachers. (5) The most significant influences as follows be In service training, motivation, and work environment to the performance of teachers at elementary school in District Pulokulon Residence Grobogan.This research is for the teacher at elementary school in District Pulokulon Residence Grobogan. 2009. Population this research are 503 persons.in this research the writer used Census Method among populations as an obyect of the research, and all populations as respondent are 50 persons. The conclusion of the research: Hypothesis (1) â€œthere is a significant correlation between in the service training to the performance of teacher at elementary school in District Pulokulon Residence Groboganâ€ is true. (2) â€œthere is a significant correlation between motivation to the performance of teacher at elementary school in District Pulokulon Residence Groboganâ€ is true. (3) â€œthere is a significant correlation between the work environment to the performance of teacher at elementary school in District Pulokulon Residence Groboganâ€ is true. (4) â€œthere is a significant correlation between in the service training, motivation, and work environment to the performance of teacher at elementary school in District Pulokulon Residence Groboganâ€ is true.(5) â€œthat itâ€™s known that variable of in service training has the most influence to the performance of teacher at elementary school in District Pulokulon Residence Groboganâ€ Keywords: In Service Training, Motivation, and Work Environment and Performance.